Current‐Induced Spin Torques on Single GdFeCo Magnetic Layers. Issue 12 (19th February 2021) - Céspedes‐Berrocal, David; Damas, Heloïse; Petit‐Watelot, Sébastien; Maccariello, Davide; Tang, Ping; Arriola‐Córdova, Aldo; Vallobra, Pierre; Xu, Yong; Bello, Jean‐Loïs; Martin, Elodie; Migot, Sylvie; Ghanbaja, Jaafar; et al.
Abstract: Spintronics exploit spin‐orbit coupling (SOC) to generate spin currents, spin torques, and, in the absence of inversion symmetry, Rashba and Dzyaloshinskii–Moriya interactions. The widely used magnetic materials, based on 3d metals such as Fe and Co, possess a small SOC. To circumvent this shortcoming, the common practice has been to utilize the large SOC of nonmagnetic layers of 5d heavy metals (HMs), such as Pt, to generate spin currents and, in turn, exert spin torques on the magnetic layers. Here, a new class of material architectures is introduced, excluding nonmagnetic 5d HMs, for high‐performance spintronics operations. Very strong current‐induced torques exerted on single ferrimagnetic GdFeCo layers, due to the combination of large SOC of the Gd 5d states and inversion symmetry breaking mainly engineered by interfaces, are demonstrated. These "self‐torques" are enhanced around the magnetization compensation temperature and can be tuned by adjusting the spin absorption outside the GdFeCo layer. In other measurements, the very large emission of spin current from GdFeCo, 80% (20%) of spin anomalous Hall effect (spin Hall effect) symmetry is determined. This material platform opens new perspectives to exert "self‐torques" on single magnetic layers as well as to generate spin currents from a magnetic layer. Abstract : A new platform is proposed for spintronics. GdFeCo/Cu bilayers are found to be 20 times more efficient than Pt layers to generate spin currents from charge currents. It is also shown that these spin currents create strong "self‐torques" on GdFeCo without the need of heavy metal. This work opens up another way to control the magnetic state of devices.